The 'Hyperbola of Quantum Chemistry': the Changing Practice and Identity of a Scientific Discipline in the Early Years of Electronic Digital Computers, 1945-65. - PARK, BUHM SOON (Annals of Science, 2003)
In 1965, John A. Pople presented a paper entitled 'Two-Dimensional Chart of Quantum Chemistry' to illustrate the inverse relationship between the sophistication of computational methods and the size of molecules under study. This chart, later called the 'hyperbola of quantum chemistry', succinctly summarized the growing tension between the proponents of two different approaches to computation-the ab initio method and semiempirical method-in the early years of electronic digital computers. Examining the development of quantum chemistry after World War II, I focus on the role of computers in shaping disciplinary identity. The availability of high-speed computers in the early 1950s attracted much attention from quantum chemists, and their community took shape through a series of conferences and personal networking. However, this emerging community soon encountered the problem of communication between groups that differed in the degree of reliance they placed on computers. I show the complexity of interactions between computing technology and a scientific discipline, in terms of both forming and splitting the community of quantum chemistry.